Afyon Karahisar, Sandıklı, Bolvadin, Çay, İsaklı, Manisa, Birgi, Muğla, Milas, Peçin, Denizli, Isparta, Atabey ve Eğirdir’deki kitabeler ve Sahip, Saruhan, Aydın, Menteşe, İnanç, Hamit Oğulları hakkında malûmat - Uzunçarşılıoğlu, İsmail Hakkı, 1888-1977. ([Ankara])
289, [74] s.